Teaching Beliefs on Developmentally Appropriate Practice Among Chinese Preschool Teachers: The Role of Personality - Wong, Paul Yau-Ho (Frontiers in Psychology, 2019)
Research has shown that teachers’ personality is related to their teaching practices. However, few such research has been conducted in the preschool settings. This research adopted a cross-sectional quantitative approach to examine how preschool teachers’ personality related to their beliefs of Developmentally Appropriate Practice (DAP). 544 preschool teachers were randomly selected to complete Teacher Beliefs and Practices Survey (TBS) and the Myer-Briggs Type Indicator (MBTI). Findings showed that the personality type profiles of preschool teachers are characterized predominantly by Sensing-Feeling-Judging. Among all personality types, extraverted and intuitive teachers tended to show higher scores in DAP beliefs and practice than that of the introverted teachers. Analyses from regression findings also indicated that the Extroversion-Introversion dimension predicted significantly teachers’ beliefs and practices of DAP. In addition, teachers’ teaching experiences in association with personality predicted their DAP practices, suggesting that there was an combined effect of teachers’ personality and work experience in adopting DAP. Implication for school managers to provide professional development to support teachers in understanding and practicing DAP in preschools are discussed.